EVALUATION OF THE TOXICOLOGICAL PROFILE OF THE LEAVES AND YOUNG TWIGS OF CAESALPINIA BONDUC (LINN) ROXB - Ogunlana, Olubanke O.; Ogunlana, Oluseyi E.; Adeneye, Adejuwon A.; Udo-Chijioke, O. A.C.; Dare-Olipede, T. I.; Olagunju, Joseph A.; Akindahunsi, Afolabi A. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Acute and sub-acute toxicological effects of ethanolic extract of the leaves and young twigs of Caesalpinia bonduc were carried out on albino rats. Single extract doses from 2000 to 5000 mg/kg body weight were administered orally and monitored for 14 days in acute study, while extract doses from 200 to 1600 mg/kg body weight were orally administered daily for 28 days in sub-acute study and recovery was assessed 14 days after dosing. Biochemical, haematological and histopathological examinations were carried out. There was no mortality in the experimental animals in all acute treatment doses. However, there were significant alterations in the biomarkers and induced cellular damage to the liver in all acute treatment doses. In the sub-acute toxicity treatment, the assessed biomarkers were unaffected at extract dose of 200 mg/kg body weight compared to control, while significant changes were observed in rats administered with extract doses of 400 mg/kg body weight and above. No significant difference was observed between the tested groups and the recovery groups in the sub-acute toxicity study. In conclusion, the ethanolic extract of C. bonduc could be toxic to selected organs of the rat body in acute and sub-acute treatments.